The French Pre-Deployment Advanced Course in Anesthesia and Resuscitation: Development and Future Prospects. Issue 7 (1st July 2021) - Py, Nicolas; Martinez, Thibault; Boyé, Matthieu; Tourtier, Jean-Pierre; Meaudre, Eric; Benbrika, Widad; Ausset, Sylvain; Pasquier, Pierre
ABSTRACT: Introduction: Military anesthesiologists from the French Military Medical Service (FMMS) are part of the Forward Surgical Teams deployed in overseas military operations. The practice of anesthesia in combat zones requires specific skills that are not taught during the initial curriculum for French civilian anesthesiologist. The Pre-Deployment Advanced Course in Anesthesia and Resuscitation (DACAR) program was developed to prepare military anesthesiologist from the FMMS before their deployment in overseas military operations. Methods: Created in 2013 by the French Military Medical Academy, the DACAR program is divided into two modules and carried out once a year. The DACAR program trains all military anesthesiologist residents at the end of their curricula. Since 2019, a number of Certified Registered Nurse Anesthetists have completed the DACAR program. The DACAR program is organized around the main axes of experience feedback from previous deployments in combat zones as well as didactic learning and practical training using high-fidelity simulation. Results: Since 2013, a total of 99 trainees completed the DACAR program during six complete cycles of two modules. The DACAR program has gradually been enriched from 14 courses in 2013 to 28 in 2019. Participants' reported satisfaction rates have increased steadily since 2016, when 88% of courses were rated as "interesting" or "very interesting, " and only 4% as "not very interesting." By 2019, those figures had improved to 96% and 2%, respectively. Conclusion: The DACAR program is a structured and adapted military medical course aimed at completing the curriculum of military anesthesiologists from the FMMS before deployment in overseas military operations. Regular audits and updates ensure that the DACAR training program maintains the highest standards of quality and rigor.